Mencit sebagai Model Penelitian: Memahami Aktivitas Pencernaan melalui Teknik Gastric Emptyinge Activity through the Gastricc Emptying Technique - Risa Umami; Zakiaturrahmah (Bioindikator: Jurnal Biologi dan Pendidikan Biologi, 2025)
The Contextual Teaching and Learning (CTL) learning model is a learning model that can connect subject matter with students' real lives, to improve creative thinking skills. The purpose of this study was to determine the effect of the Contextual Teaching and Learning learning model on Integrated Science subjects on the creative thinking skills of class VIII students at MTs AL-Muslimun NW Tegal. The type of research used in this study was a quasi-experiment with a Nonequivalent control group design. Sampling used a saturated sample type. The research sample consisted of 24 students for the experimental class, and 24 students for the control class. The data collection technique in this study used a descriptive test instrument. The hypothesis proposed in this study is that there is an effect of the Contextual Teaching and Learning learning model on Integrated Science subjects on students' Creative Thinking Skills. The results showed that the use of the Contextual Teaching and Learning learning model on Integrated Science subjects on creative thinking skills has a significant difference with conventional learning. Based on the data obtained through the pretest, the two classes had average scores that were not much different. The experimental class had an average score of 40.42. While the pretest score in the control class had an average score of 35.21. After being given treatment, the average score of the experimental class was much better compared to the control class. Based on the data obtained through the posttest, the experimental class had an average score of 74.79. While the posttest score of the control class had an average score of 54.42. Based on the data obtained through the pretest and posttest in the experimental class and the control class, the results of the achievement of creative thinking skills indicators in the control class were only in the original indicator that could reach the very creative category using conventional learning, namely 80.72% in the very creative category, while in the experimental class there were two indicators that could reach the very creative category, namely flexible thinking 82.29% in the very creative category and original thinking 72.39% in the very creative category using the Contextual Teaching and Learning learning model towards students' creative thinking skills.